Did we overestimate the role of social preferences? The case of self-selected student samples - Armin Falk; Stephan Meier; Christian Zehnder (Center for Economic Studies and ifo Institute (CESifo), 2010)
Social preference research has fundamentally changed the way economists think about many important economic and social phenomena. However, the empirical foundation of social preferences is largely based on laboratory experiments with self-selected students as participants. This is potentially problematic as students participating in experiments may behave systematically different than non-participating students or non-students. In this paper we empirically investigate whether laboratory experiments with student samples misrepresent the importance of social preferences. Our first study shows that students who exhibit stronger prosocial inclinations in an unrelated field donation are not more likely to participate in experiments. This suggests that self-selection of more prosocial students into experiments is not a major issue. Our second study compares behavior of students and the general population in a trust experiment. We find very similar behavioral patterns for the two groups. If anything, the level of reciprocation seems higher among non-students implying an even greater importance of social preferences than assumed from student samples.
Keywords: C90; D03; 330; methodology; selection; experiments; prosocial behavior; Soziale Wohlfahrtsfunktion; Austauschtheorie (Soziologie); Experimentelle Ökonomik; Studierende; Wissenschaftliche Methode; Vertrauen; Test